The theme of tragedy in modern Uzbek poetry (in works of Halima Ahmedova, Zebo Mirzo, Nodira Afokova) (Zien Journal of Social Sciences and Humanities, 2022)
The article examines the extent of tragedy in the work of our Uzbek female poets and highlights its general aspects